(untitled) (KYAMC Journal, 2021)
Background: Disorders of musculo-skeletal (MSK) system are very common scenario watched in diabetic patients and is a major cause of morbidity, mortality and hospitalization. Objective: The present study to see the pattern of MSK disorders among the Bangladeshi diabetic patients. Materials & Methods: This is a cross-sectional study carried out at the department of Physical Medicine and Rehabilitation in Thengamara Mohila Sabuj Sangha (TMSS) Medical College Hospital, Bogura for the period of one year from February 2019 to January 2020. A total of 450 diabetic patients with MSK disorders were included in this study. Results: A total of 450 patients with MSK disorders were studied. Out of them 208 (46%) were males and 242(54%) were females.31.5% were between the age group of 41-50 years and 28.9% was between 51-60years.Majority were housewives (51.2%) followed by cultivator(16.2%).Degenerative joint diseases were more common (31.4%) than inflammatory arthropathies (19.3%).Lumbar and cervical spondylosis constituted about 31.4% of all disorders& 22.7% presented with OA knee whereas 15.6% presented with rheumatoid arthritis. Conclusion: Degenerative disorders of the MSK system are more common than the inflammatory ones amongst the diabetics.Maximum patients were having OA of knee, lumbar spondylosisand soft tissue rheumatism. KYAMC Journal.2021;12(1): 41-43